Controls on the Precipitation of Carbonate Minerals Within Marine Sediments - Turchyn, Alexandra V.; Bradbury, Harold J.; Walker, Kathryn; Sun, Xiaole (Frontiers in Earth Science, 2021)
The vast majority of carbonate minerals in modern marine sediments are biogenic, derived from the skeletal remains of organisms living in the ocean. However, carbonate minerals can also precipitate abiotically within marine sediments, and this carbonate mineral precipitation within sediments has been suggested as a third major, and isotopically distinct, sink in the global carbon cycle, particularly important earlier in Earth history . Here we present a global compilation of pore fluid data and compare the sulfate, calcium, phosphate and magnesium concentrations with pore fluid alkalinity to explore the emerging relationships and explore what drives carbonate mineral precipitation in sediments. Our data compilation shows that the gradient of pore fluid sulfate concentrations correlates strongly with the gradient of alkalinity as well as with the gradient of calcium, and that these correlations improve dramatically in sediments where methane is present. We also note that sedimentary pore fluids that are high in phosphate concentration are also high in alkalinity, which may indicate suppression of carbonate mineral precipitation in the presence of sedimentary phosphate. Our data can be used to highlight sediments where both dolomite formation and dolomitization of previously deposited calcium carbonate minerals is occurring. We explore how carbonate mineral saturation state changes as a function of calcium concentrations, alkalinity, and pH, and suggest a reason why calcium concentrations are never fully depleted in sedimentary pore fluids. We conclude that carbonate minerals precipitate in sediments with methane, where the anaerobic oxidation of this methane helps promote particularly high saturation states for carbonate minerals.